Schoolwide Systems of Positive Behavior Support: Implications for Students at Risk and With Emotional/Behavioral Disorders - Lewis, Timothy J.; McIntosh, Kent; Simonsen, Brandi; Mitchell, Barbara S.; Hatton, Heather L. (AERA open, 2017)
The use of schoolwide multitiered systems of support to address challenging social and emotional behavior has been established in >20,000 schools across the United States and 19 other countries worldwide. The systems approach of schoolwide positive behavior support is guided by implementation science and embeds evidence-based behavioral interventions across a continuum based on documented student need. The extant research base to date, including randomized controlled trials, is robust with respect to universal or Tier I interventions and supports. Less is known about the impact on students who are at high risk for manifesting a disability, as well as those currently served under the Individuals with Disabilities Education Act. The purpose of this article is to provide a rationale for, and overview of, schoolwide positive behavior support as a comprehensive framework to support children and youth with emotional/behavioral disorders and review the research to date across a continuum of supports. Research, professional development and implementation, and policy implications are discussed.